Biomaterials in 3D Printing: A Special Emphasis on Nanocellulose - Badhe, Ravindra Vijay; Godse, Anagha; Ahinkar, Ankita (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim and Background: The main objective of this review is to highlight nanocellulosic materials in 3D bioprinting. Three-dimensional (3D) bioprinting is on the verge of fabricating the artificial organ and living tissues. For the target construction the process of this 3D bioprinting involves layer-by-layer deposition of suitable biomaterials using predesigned data made by using Computer Aided Design (CAD) as an outline. However, only a handful of biomaterials are able to fulfil the considerable requirements for suitable bioink formulation, which is a critical component of efficient 3D bioprinting. Conclusion: Cellulose, a naturally occurring polysaccharide, is clearly the most commonly employed material in current bioinks. Here, in this review we discuss the advantages, reasons, applications, disadvantages of the use of cellulosic bioink in 3D bioprinting by summarizing the most recent studies that used cellulose for printing vascular tissue, bone and cartilage. In addition, other breakthroughs in the use of cellulose in bioprinting are discussed, including strategies to improve its structural and degradation characteristics. In this review, we organize the available literature in order to inspire and accelerate novel cellulose-based bioink formulations with enhanced properties for future applications in basic research, drug screening and regenerative medicine.
Keywords: Cellulose; Bioprinting; Regenerative medicine; Biomaterials; Bioink